2015
DOI: 10.1038/ncomms7798
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic imaging of the growth plate cartilage reveals multiple contributors to skeletal morphogenesis

Abstract: The diverse morphology of vertebrate skeletal system is genetically controlled, yet the means by which cells shape the skeleton remains to be fully illuminated. Here we perform quantitative analyses of cell behaviours in the growth plate cartilage, the template for long bone formation, to gain insights into this process. Using a robust avian embryonic organ culture, we employ time-lapse two-photon laser scanning microscopy to observe proliferative cells' behaviours during cartilage growth, resulting in cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 35 publications
0
56
0
Order By: Relevance
“…Matrix production and accumulation are also important for interstitial growth. Cell hypertrophy greatly increases the tissue space, which is suggested to be responsible for the longitudinal tissue volume . In addition, recent studies have indicated that growth plate chondrocytes serve as osteoprogenitors and directly contribute to trabecular and cortical bone formation …”
Section: Introductionmentioning
confidence: 99%
“…Matrix production and accumulation are also important for interstitial growth. Cell hypertrophy greatly increases the tissue space, which is suggested to be responsible for the longitudinal tissue volume . In addition, recent studies have indicated that growth plate chondrocytes serve as osteoprogenitors and directly contribute to trabecular and cortical bone formation …”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in 4D-microscopy imaging and cell tracking tools permit now simultaneous measurements at high spatial-temporal coverage and resolution, and therefore the assessment of cell lineages and cell behaviors including displacements and proliferations (Amat et al, 2014; Blanpain and Simons, 2013; Faure et al, 2016; Keller, 2013; Li et al, 2015; Olivier et al, 2010; Truong et al, 2011). Thus, it is time to progress in filling the void between gene regulatory networks and tissue architecture.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Armbruster et al developed designer receptors which could be activated by a designer drug (DREADD) encoded on retroviral vectors pBabepuro, which could be used to probe whole-brain functional networks and behaviors of specific cell types stimulated and inhibited by chemicals 93,94 . This method has demonstrated high-resolution, enabling identification of heterogeneities of basal ganglia pathway, selective functional activation of the extended amygdala circuit and many tasks which could not be easily achieved by PETs 95 [103][104][105] , and plant viruses, such as cowpea chlorotic mottle virus (CCMV) 106 and cowpea mosaic virus (CPMV) [107][108][109] .…”
Section: Viral Vectors For Probing Living Cellsmentioning
confidence: 99%